Diversity of insect at paddy field in Pekan Kandang Melaka / Khairul Anwar Abu Bakar and Ismail Rakibe - Abu Bakar, Khairul Anwar; Rakibe, Ismail (Faculty of Plantation and Agrotechnology, 2018)
Diversity and abundance of insect vary in ecosystem of paddy because of the difference growing stages of paddy as well as its abiotic and biotic factors. Insect diversity studies were conducted in paddy plots planted organically under variety CL220 at Pekan Kandang Melaka. Eight sampling with interval of five days visits were made from late July 2018 to early September 2018. Two sampling method were used which is yellow sticky trap and yellow pan trap. A total of 25 families and 9 orders of insect were recorded comprising Hemiptera, Coleoptera, Orthoptera, Homoptera, Lepidoptera, Hymenoptera, Odonata, Diptera and Araneae. For the total sampling period, the Shannon-Wiener diversity index (H’) is 0.36 for both yellow sticky trap and yellow pan trap. The most abundance insect order for yellow sticky trap were Hemiptera (43%) the lowest was Odonata (1.8%). For the yellow pan trap, the most abundance insect also from order Hemiptera (41%) and the lowest wass Lepidoptera (3%). Several species from order Hemiptera which is Nilaparvata lugens and Nephotettix virescens are known as serious pest of paddy in this area and has highest population caught during the study by both method of traps. The pesticide usage by farmers also cause the adverse effect toward beneficial insect population such as Agriocnemis pygmaea (Odonata). These shows that the abundance of insect bring impact to paddy growth.